2022
DOI: 10.20944/preprints202212.0449.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behind the Curtain: In silico and in vitro Experiments Brought to Light New Insights Into the Anticryptococcal Action of Synthetic Peptides

Abstract: Cryptococcus neoformans threaten the health, causing cryptococcal meningitis and pneumonia, especially in immunosuppressed patients, which can be fatal. Recently, our research group evaluated and studied the mechanisms of action of four synthetic peptides (SP) against C. neoformans. Here, in silico and in vitro analyses help deepen understanding of peptides' mechanisms of action. The interaction of the peptides with a membrane receptor was analyzed by docking analysis, in addition to ROS overproduction and the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(70 reference statements)
0
2
1
Order By: Relevance
“…These data suggest the activity and mechanism of action of Mo-CBP3-PepII are dependent on ROS accumulation. This result is different from others presented by peptides RcAlb-PepIII and PepKAA [21], where the ability of pore formation is independent of ROS.…”
Section: Mo-cbp3-pepii Affects the Activity Of Redox System Enzymescontrasting
confidence: 99%
See 2 more Smart Citations
“…These data suggest the activity and mechanism of action of Mo-CBP3-PepII are dependent on ROS accumulation. This result is different from others presented by peptides RcAlb-PepIII and PepKAA [21], where the ability of pore formation is independent of ROS.…”
Section: Mo-cbp3-pepii Affects the Activity Of Redox System Enzymescontrasting
confidence: 99%
“…Recently, it was reported that two synthetic peptides, RcAlb-PepII and PepGAT, lost the ability to induce pore formation in the C. neoformans membrane in the presence of an antioxidant agent where no H2O2 accumulation. This result suggests both peptides induce pore formation by ROSdependent pathway [21]. Besides damaging the membrane, higher levels of H2O2 could also result in a higher level of oxidized protein and loss of activity.…”
Section: Mo-cbp3-pepii Induced Ros Overaccumulation In C Neoformans C...mentioning
confidence: 88%
See 1 more Smart Citation